La semiótica en Chile - Villar Muñoz, Rafael del (Signa: Revista de la Asociación Española de Semiótica, 2022)
There are three historical periods in the Chilean semiotics. The first one corresponds to its birth (1969) associated with the ideological fight of society as a whole. The second one (1975-1982) corresponds to the hegemony of an epistemological field whose fundamental demands are the gaps in specific theoretical fields: the literature and the visual aesthetics. The third period (1981 to this day), that incorporates a new epistemological region: the communications develops a rupture with the previous field, the questions are no longer originated in the theory but in the productive structure of society.